Use of MRI in the Diagnosis of Fetal Brain Abnormalities in Utero (MERIDIAN): A Multicenter, Prospective Cohort Study. Issue 4 (December 2017) - Griffiths, Paul D.; Bradburn, Michael; Campbell, Michael J.; Cooper, Cindy L.; Graham, Ruth; Jarvis, Deborah; Kilby, Mark D.; Mason, Gerald; Mooney, Cara; Robson, Stephen C.; Wailoo, Allan
Abstract : ( Lancet . 2017;389:538–546) Ultrasonography is the predominant mode of antenatal screening for fetal brain abnormalities. It has been suggested that in-utero magnetic resonance imaging (iuMRI) in conjunction with ultrasound examination could further improve diagnosis of these abnormalities. The magnetic resonance imaging (MRI) to enhance the diagnosis of fetal developmental brain abnormalities in utero (MERIDIAN) study was a prospective, cohort study undertaken at multiple centers in the United Kingdom to assess whether using iuMRI improved the accuracy and confidence of diagnoses of fetal brain abnormalities relative to using ultrasound alone. Effects of iuMRI on clinical management as well as women's acceptance of the MRI examination were also evaluated.